2013
DOI: 10.1371/journal.pone.0054795
|View full text |Cite
|
Sign up to set email alerts
|

Local Delivery of Cannabinoid-Loaded Microparticles Inhibits Tumor Growth in a Murine Xenograft Model of Glioblastoma Multiforme

Abstract: Cannabinoids, the active components of marijuana and their derivatives, are currently investigated due to their potential therapeutic application for the management of many different diseases, including cancer. Specifically, Δ9-Tetrahydrocannabinol (THC) and Cannabidiol (CBD) – the two major ingredients of marijuana – have been shown to inhibit tumor growth in a number of animal models of cancer, including glioma. Although there are several pharmaceutical preparations that permit the oral administration of THC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 41 publications
0
66
0
1
Order By: Relevance
“…This is as an area where there is a notable lack of information, as previous studies investigating the action of cannabinoids in glioma have only been carried out in xenograft models (13,14). Our hypothesis was that cannabinoids could support the cell killing effect of irradiation by engaging and/or priming apoptosis and autophagy mechanisms required for successful cell death.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This is as an area where there is a notable lack of information, as previous studies investigating the action of cannabinoids in glioma have only been carried out in xenograft models (13,14). Our hypothesis was that cannabinoids could support the cell killing effect of irradiation by engaging and/or priming apoptosis and autophagy mechanisms required for successful cell death.…”
Section: Discussionmentioning
confidence: 98%
“…This nonantagonistic interaction of CBD and THC, therefore, suggested that combining cannabinoids with other agents that share common pathways may be a viable strategy in a clinical setting; this may also include more conventional chemotherapies (4,11). Indeed, recent studies have highlighted that CBD and THC can combine successfully with other chemotherapy, namely temozolomide, to reduce the progression of glioma cells in a xenograft model (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El mecanismo de acción antitumoral se basa en la capacidad de estos compuestos para: (i) promover la muerte apoptótica de las células cancerosas, (ii) inhibir la angiogénesis del tumor y (iii) reducir la migración de las células cancerosas. Se ha propuesto que la apoptosis inducida por éste se basa en un aumento de la producción de especies reactivas de oxígeno, un mecanismo que parece funcionar también en células de glioma 10 .…”
Section: Receptores Cannabinoidesunclassified
“…Cannabinoids promote tumor regression by modulating signaling pathways involved in processes such as cell cycle progression, cell proliferation, cell death, angiogenesis and metastasis, migration and invasion, and epithelialmesenchymal transition [5,[36][37][38]. It is well known that cannabinoids are capable of inducing cell cycle arrest in all phases [39].…”
Section: Activation Of Cbr Induces 14-3-3β-mediated Signalingmentioning
confidence: 99%